Evaluación de métodos fermentativos de cacao Nacional y CCN51 usando yute, cajas Rohan y microorganismos para mejorar propiedades sensoriales - Cevallos Castillo, Carmen Anais (2025)
This study evaluated the impact of two fermentation methods (Rohan boxes and jute bags) and three levels of mountain microbial induction (0%, 30%, and 60%) on the physicochemical and sensory properties of Ecuadorian cacao varieties Nacional and CCN51, using a three-factor experimental design. The results demonstrated that fermentation in Rohan boxes with 60% microbial induction significantly optimized the cacao's sensory profile, achieving a score of 8.4/9 in aroma, flavor, and texture, and 83.6% well-fermented beans, surpassing the non-induced control (6.1/9 and 58.3%, respectively). Furthermore, stable fermentation conditions were observed (temperatures of 45.8°C to 49.5°C, final pH of 5.0 to 5.2, and Brix levels above 16.3), which favored a more uniform and controlled fermentation. The physicochemical quality of the beans also showed significant improvements, especially in the levels of bioactive compounds, with an antioxidant capacity of up to 89.27% in the optimal treatment. Furthermore, it was shown that the interaction between the type of fermenter and the percentage of microbial induction directly influenced the reduction of defects such as flat, purple, and slate-like beans, and promoted greater homogeneity in the bean's organoleptic attributes. This biotechnological approach not only improves cacao quality but also represents a sustainable and adaptable alternative for small producers by leveraging native microorganisms. Together, these findings highlight the potential of directed fermentation as a key tool for improving the Ecuadorian cacao value chain